Les représentations de l’île Maurice dans l’imaginaire littéraire franco‑mauricien - Wiśniewska-Szaran, Katarzyna (Romanica Silesiana)
Mauritius is a small island in the Indian Ocean, whose population approximates to that of Warsaw. Since its discovery, the island was ruled by several governments: Dutch, French, and English, before it finally became independent in 1968. On this piece of land of about 2,000 m2 live direct descendants of the inhabitants of three continents: Europe, Africa and Asia. The history of the island and the Mauritian people create its specificity. Undoubtedly, the fact that Mauritius is an island largely influences the Mauritian society. In my article, I will study how this impacts on the society, including its writers. I will seek to define the nature of their relationships. I will try to describe the various representations of the island in Franco‑Mauritian literary fiction at the turn of the twentieth and twenty‑first centuries. Since this topos is in dichotomy of good and evil, I will consider the island as a synonym of a half‑paradise and a half‑prison. Subsequently, I will analyse it as a character of its own. Finally, I will argue that Mauritius can be seen as a reflection of the world, a miniature model. In summary, after examining the various images of Mauritius, I will try to demonstrate its special status in the Mauritian society, especially in literature. Key words: Mauritian society, insularity, Franco‑Mauritian literary fiction